In situ space-confined growth of Co3O4 nanoparticles inside N-doped hollow porous carbon nanospheres as bifunctional oxygen electrocatalysts for high-performance rechargeable zinc–air batteries. Issue 14 (13th March 2023) - Kuang, Jingbiao; Yu, Nengfei; Yang, Zhongtang; Zhang, Yi; Ji, Lifei; Ye, Jilei; Huang, Wen; Huang, Qinghong; Tian, Na; Wu, Yuping; Sun, Shigang
Abstract : Co3 O4 -10%@N-HPCNs with high surface area, hollow porous structure and strong interaction between nanoparticles and carbon nanospheres provide sufficient reactive sites and charge/mass transport environment, resulting in improved performance of RZABs. Abstract : Developing high-performance and low-cost bifunctional oxygen electrocatalysts for both the oxygen reduction reaction (ORR) and the oxygen evolution reaction (OER) is of great significance for accelerating the commercialization of rechargeable zinc–air batteries (RZABs). Herein, in situ grown Co3 O4 nanoparticle-embedded N-doped hollow porous carbon nanospheres (Co3 O4 @N-HPCNs) are synthesized via template-assisted pyrolysis as efficient bifunctional ORR/OER electrocatalysts. The N-HPCNs efficiently seize and confine Co3 O4 nanoparticles to enhance electronic conductivity and structural stability, while the hollow porous architecture offers adequate mass diffusion pathways to improve the accessibility of reactants and electrolytes on active sites. Therefore, the as-obtained Co3 O4 -10%@N-HPCNs display outstanding activity and stability for the ORR and the OER, even outperforming commercial Pt/C and Ru/C catalysts. Liquid RZABs assembled with Co3 O4 -10%@N-HPCN cathodes exhibit a large specific capacity of 768.3 mA h g −1 Zn, a high peak power density of 145.6 mW cm −2 and a long-term cycling stability for over 1000 h, demonstrating much-enhanced battery performance in comparison with that of Pt/C + Ru/C based RZABs. Also, flexible quasi-solid-state RZABs assembled with Co3 O4 -10%@N-HPCN cathodes exhibit a considerable power density of 132.0 mW cm −2 and a stable charge–discharge voltage for a long period even upon bending. This work provides a new approach for the development of catalysts with high activity, long-term stability and low cost.